Characterization and primary recovery of funtional bioactive compounds from edible bird's nest - Lim, Hong Kwong (2014)
The edible bird’s nest (EBN) is a saliva-cemented nest built by swiftlets (Collocalia spp. /Aerodramus spp.) during the breeding season, and it is found predominantly in Southeast Asia. However, little is known or is published about EBN and no scientific and technological findings on recovering bioactive compounds from EBN. Therefore, this study was conducted to characterize the physico-chemical, rheological behavior properties and recover the functional biocompounds derived from EBN. The application of an aqueous two-phase system (ATPS) strategy to the potential recovery of bio-compounds (sialoglycoproteins) from the EBN was evaluated. This study revealed that the amino acid composition of EBN-extract was significantly higher (P < 0.05) than that of intact EBN, with the exception of the methionine content. Overall, the most abundant amino acids in the chemical structure of EBN-extract were aspartic acid (9.80 %), serine (9.50 %), and proline (8.81 %). The hydrophilic glycoprotein in EBN-extract was a heavily glycosylated protein, and this result was further supported by the presence of two glycoprotein bands at 110 and 130 kDa, as observed by SDSPAGE analysis. The non-Newtonian flow behavior of Collocalia mucoid (EBNextract) dispersions indicated that all concentrations (5 – 100 mg/mL) of the mucoid dispersions exhibited shear-thinning behaviors, which could best be described using the Herschel-Bulkley model. As the concentration of Collocalia mucoid dispersions increased, the appearance of a plateau shear modulus indicated the dispersion was exhibiting more gel-like behaviors. The Collocalia mucoid dispersions were thought to involve the physical entanglement of network formations, which were able to form weak gels at high concentrations. The effects of hydrophilic solvent in the ATPS and the system parameters on partition behavior were evaluated. The partitioning of the EBN sialoglycoprotein was pHdependant. Slightly more than 97 % of the total EBN sialoglycoproteins were recovered in the top phase of ATPS under selected conditions. According to this study, the ATPS technique provides a simple, efficient, and economic recovery process for sialoglycoproteins derived from EBN and EBN by-products for the food, nutraceutical, pharmaceutical, cosmetic, and other related industries. This ATPS separation technique has great potential to be carried over to an industrial scale.